2017
DOI: 10.1017/wet.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Chlorophyll Fluorescence Imaging Technology to Detect Plant Injury by Herbicides in Sugar Beet and Soybean

Abstract: Sensor technologies are expedient tools for precision agriculture, aiming for yield protection while reducing operating costs. A portable sensor based on chlorophyll fluorescence imaging was used in greenhouse experiments to investigate the response of sugar beet and soybean cultivars to the application of herbicides. The sensor measured the maximum quantum efficacy yield in photosystem II (PS-II) (Fv/Fm). In sugar beet, the averageFv/Fmof 9 different cultivars 1 d after treatment of desmedipham plus phenmedip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
(43 reference statements)
3
19
0
Order By: Relevance
“…The F v /F m value is a good proxy of plant health www.scienceasia.org status [32]. In the present study, a reduction in F v /F m values was observed in both creepers under high-temperature stress; further, the ratio decreased continuously with the prolongation of the stress.…”
Section: Discussionsupporting
confidence: 58%
“…The F v /F m value is a good proxy of plant health www.scienceasia.org status [32]. In the present study, a reduction in F v /F m values was observed in both creepers under high-temperature stress; further, the ratio decreased continuously with the prolongation of the stress.…”
Section: Discussionsupporting
confidence: 58%
“…Wang et al [ 19 , 20 ] developed a mobile sensor from a chlorophyll fluorescence imaging system, which could be applied in the greenhouse and field tests. It has been applied for the early detection of the effects of herbicide on a commercially sensitive population of Alopecurus myosuroides and for herbicide stress detection in soybeans, a crop which is very sensitive to the tested herbicides [ 21 , 22 ]. However, further investigation is required to test its ability to identify herbicide resistance, for the greenhouse and field application, and on a wider range of weed species.…”
Section: Introductionmentioning
confidence: 99%
“…vulgaris) and soybean (Glycine max (L.) Merr. ), Weber et al (2017) examined nine sugar beet and seven soybean cultivars with Table 4 Maximum quantum yield of photosystem II (F v /F m ) of sensitive (S) and resistant (R) Stellaria media (L.) Vill. plants 4 days after treatment in comparison with the accuracy of the discriminant maximum likelihood classifiers…”
Section: Herbicide Induced Stress In Cropsmentioning
confidence: 99%
“…In the past four decades, several optical sensor systems have been developed to support farmers and consultants by identifying crop stress response to fungal infections and diseases, weed competition and pests (Peteinatos et al 2016). Sensors have also been used to detect phytotoxic side effects of pesticides, mainly herbicides in crops (Weber et al 2017). Pests, fungal diseases and weeds can be controlled with lower pesticide rates, when they are detected at an early stage of development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation